Penerapan Pengendalian Internal atas Sistem Pengeluaran Kas pada PT. Varia Usaha Beton - Anty Wulandari; R. Muh. Syah Arief Atmaja Wijaya (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2023)
The business must be able to handle every aspect of its operations and attempts to solve any issues in order to stay current with advances in the industrial field. Any decisions that affect a company's money or assets must be managed. One of the assets of the business that has to be handled is cash. Cash is vulnerable to deception since it contains qualities that may be readily transferred. Cash carries the danger of fraud, especially employee dishonesty. This research aims to determine whether internal control at PT. Varia Usaha Beton over the cash distribution system conforms with the COSO concept of internal control. COSO is the Committee of Sponsoring Organizations of the Treadway Commission. This study adopted a qualitative descriptive methodology, and data were gathered through observation, interviews, and documentation. The findings of this study show that PT. Varia Usaha Beton's internal control over its cash disbursement system has shown to be fairly successful. This is so that all of the internal control requirements set out by COSO, including control environment, risk assessment, control activities, information and communication, and monitoring, have been met by the firm.